The Effect Of 5E Learning Cycle Models Containing Science Literacy on Students’ Learning Competencies in Additives and Addictive Substances Material at Junior High School 18 Padang - Mutia Sari; Rahmawati Darussyamsu; Irma Leilani Eka Putri; Syamsurizal Syamsurizal (Universitas Negeri Padang, 2019)
This research is based on the problems that exist in the junior high school 18 Padang, namely the learning model that is less varied, student competence is still low, and learning is teacher centered. The effort that can be done is the application of learning cycle 5E learning model that contains scientific literacy to additives and addictive substances. The purpose of this study was to determine the effect of the learning cycle 5E with scientific literacy on the learning competencies of Grade VIII students at junior high school 18 Padang. This research is a quasi-experimental study with a randomized control group posttest only design. The study population was eighth grade students of SMP Negeri 18 Padang 2018/2019 academic year consisting of eleven classes. The research sample was taken using purposive sampling technique, the results of which were selected class VIII.3 as the experimental class and class VIII.4 as the control class. The results of data analysis found that the competency data of knowledge, attitudes, and skills of homogeneous and normal learners. Hypothesis test results are known that knowledge competencies (2,60> 1,67), competency attitudes (4,26> 1,67, and skills competency (3,33> 1,67) So it can be concluded that the learning cycle 5e model with scientific literacy has a positive effect on participants' learning competencies in additives and addictive substances in the junior high school 18 Padang. Keywords: learning cycle 5E, sains literation, learning competency.